Expanding the portfolio of tribo-positive materials: Aniline formaldehyde condensates for high charge density triboelectric nanogenerators. (January 2020) - Zhao, Pengfei; Soin, Navneet; Kumar, Amit; Shi, Lin; Guan, Shaoliang; Tsonos, Christos; Yu, Zidong; Ray, Sekhar Chandra; McLaughlin, James A.; Zhu, Zhigang; Zhou, Erping; Geng, Junfeng; et al.
Abstract: The rapid uptake of energy harvesting triboelectric nanogenerators (TENGs) for self-powered electronics requires the development of high-performance tribo-materials capable of providing large power outputs. This work reports on the synthesis and use of aniline formaldehyde resin (AFR) for energy-harvesting applications. The facile, acidic-medium reaction between aniline and formaldehyde produces the aniline-formaldehyde condensate, which upon an in-vacuo high temperature curing step provides smooth AFR films with abundant nitrogen and oxygen surface functional groups which can acquire a tribo-positive charge and thus endow AFR with a significantly higher positive tribo-polarity than the existing state-of-art polyamide-6 (PA6). A TENG comprising of optimized thin-layered AFR against a polytetrafluoroethylene (PTFE) film produced a peak-to-peak voltage of up to ~1000 V, a current density of ~65 mA m −2, a transferred charge density of ~200 μC m −2 and an instantaneous power output (energy pulse) of ~11 W m −2 (28.1 μJ cycle −1 ), respectively. The suitability of AFR was further supported through the Kelvin probe force microscopy (KPFM) measurements, which reveal a significantly higher average surface potential value of 1.147 V for AFR as compared to 0.87 V for PA6 and a step-by-step increase of the surface potential with the increase of energy generation cycles. The work not only proposes a novel and scalable mouldable AFR synthesis process but also expands with excellent prospects, the current portfolio of tribo-positive materials for triboelectric energy harvesting applications. Graphical abstract: Image 1 Highlights: Stable, mouldable aniline formaldehyde resin synthesized via low-temperature acidic-medium reaction and  in-vacuo  curing step. Aniline formaldehyde films show strong tribo-positive behaviour due to positively-charged nitrogen and oxygen surface groups. KPFM was applied to study the operation mechanism of the produced TENG based on the aniline formaldehyde and PTFE films.